Digital methodology for management of organizational and technological processes of facility construction for optimization of design parameters - Zhelezniak , Vladyslav; Kononchuk , Roman (Ways to Improve Construction Efficiency, 2024)
The article addresses the current challenges of developing a digital methodology for managing organizational and technological processes in construction, aimed at optimizing project parameters and enhancing the efficiency of investment and construction programs. In the context of increasing project complexity, strict time constraints, and the need for rational resource utilization, digital transformation becomes a decisive factor for ensuring the competitiveness of construction enterprises.The study investigates the key directions of applying digital technologies in construction, including Building Information Modeling (BIM), tools of scheduling and network planning, digital platforms for risk and resource management, and integrated project monitoring systems. It is demonstrated that the combination of methodological approaches with modern software solutions creates the foundation for flexible management of organizational and technological decisions. Such integration allows rapid adaptation to external and internal changes and minimizes the negative impact of uncertainty on project performance.Particular attention is paid to the optimization of construction duration and cost through the integration of digital tools into management processes. The research substantiates that the digital management methodology enables multifactor analysis, scenario forecasting, and the formation of adaptive organizational and technological solutions. The effectiveness of these solutions is reflected in higher labor productivity, reduced costs, minimized risks of schedule disruptions, and improved quality of construction and installation works.The paper also discusses practical aspects of applying digital methods in Ukrainian construction companies engaged in reconstruction, recovery, and the erection of new industrial and civil facilities. Emphasis is placed on the role of digitalization in coordinating stakeholder interactions, ensuring transparency in decision-making, and creating a unified information environment for managing data throughout the entire life cycle of a construction project.The findings have both theoretical and practical significance. They contribute to the further development of methodological foundations for construction organization with the use of digital technologies, as well as the formation of innovative mechanisms for project parameter optimization, ensuring high levels of efficiency and sustainability in construction projects.